Evaluation of dry deposition velocity of So2 by Bowen Ratio and resistance model over rice paddy in tropical climate - Orachorn Chimjan,; Pojanee Khummongkol, (Universiti Kebangsaan Malaysia, 2012)
The Bowen ratio method was applied to determine dry deposition velocity of SO2 over rice paddy in the tropical climate condition (hot and humid). The meteorological parameters and SO2 concentration required by the method were monitored online during July – December 2007. The deposition velocity was evaluated under the wet and dry climatic conditions. The median values of the velocity in daytime in the wet season were in ranges of 0.24 - 0.41 cm s-1, and 0.42 - 0.77 cm s-1 in the dry season. The SO2 dry deposition velocity was found to be very low for all the nighttime measurements and independent of seasonal variation. A relationship between the deposition velocity and the humidity was seen in which the SO2 velocity inversely increased with the relative humidity. The velocity determined by the Bowen ratio study was compared to Wesely resistance model. The comparative study showed that the SO2 deposition velocity obtained by the resistance model was higher than the Bowen ratio in the wet season (high humidity) but lower in the dry season (low humidity). This indicated the effect of humidity on the deposition velocity under the tropical climatology. The parameterization terms to calculate the SO2 deposition in the resistance model need to be modified for the tropical region.